Polymorphisms in the hypervariable control region of the mitochondrial DNA differentiate BPH populations - Anand, Rashi; Singh, S. Priyokumar; Sahu, Nihar; Singh, Y. Tunginba; Mazumdar-Leighton, Sudeshna; Bentur, J. S.; Nair, Suresh (Frontiers in Insect Science, 2022)
The brown planthopper (BPH; Nilaparvata lugens) is one of India’s most destructive pests of rice. BPH, a monophagous migratory insect, reported from all major rice-growing ecosystems of the country, is capable of traversing large distances and causing massive crop loss. A crucial step for developing viable management strategies is understanding its population dynamics. Very few reliable markers are currently available to screen BPH populations for their diversity. In the current investigation, we developed a combinatorial approach using the polymorphism present within the mitochondrial Control Region of BPH and in the nuclear genome (genomic simple sequence repeats; gSSRs) to unravel the diversity present in BPH populations collected from various rice-growing regions of India. Using two specific primer pairs, the complete Control Region (1112 to 2612 bp) was PCR amplified as two overlapping fragments, cloned and sequenced from BPH individuals representing nine different populations. Results revealed extensive polymorphism within this region due to a variable number of tandem repeats. The three selected gSSR markers also exhibited population-specific amplification patterns. Overall genetic diversity between the nine populations was high (>5%). Further, in silico double-digestion of the consensus sequences of the Control Region, with HpyCH4IV and Tsp45I restriction enzymes, revealed unique restriction fragment length polymorphisms (digital-RFLPs; dRFLPs) that differentiated all the nine BPH populations. To the best of our knowledge, this is the first report of markers developed from the Control Region of the BPH mitogenome that can differentiate populations. Eventually, such reliable and rapid marker-based identification of BPH populations will pave the way for an efficient pest management strategy.